Learning Videos with Gymnastic Materials on The Character of Students' Discipline and Cooperation - Nugraha, Ugi; Ilham, Ilham; Harjono, Hary Soedarto; Setiawan, Aji (LPPM Undiksha, 2023)
The use of learning media in the form of videos can be applied in physical education, sports and health lessons in teaching character of discipline. The aim of this research is to analyze student responses to PJOK learning videos, and how the influence of student responses to PJOK learning videos on the character of student disciplines and cooperation. This study uses the type of descriptive quantitative research. The subjects used in this study were students of class X and XI at senior high school. The population of this study was 70 students consisting of 35 students of class X and 35 students of class XI. Data collection method is using questionnaire of a Likert scale. Then the questionnaire data was processed using the SPSS application. Based on the results of the regression test, it can be concluded that there is an effect of student response to the PJOK learning video on the discipline and cooperation character of class X and XI students at senior high school. The implication of this research is that it can be input for teachers to see the character of students' discipline and cooperation by using learning videos on gymnastic materials.